Static and dynamic magnetic interactions in graphene and related materials - Duffy, John M. (Trinity College (Dublin, Ireland). School of Physics, 2016)
Since its discovery in 2004, graphene has been the recipient of both intense research and media attention. Graphene's properties reads as a list of superlatives, and its applications are vast and diverse. However, in this thesis, we are most interested in its potential role in spintronics. Spintronics, the field that attempts to exploit the spin of the electron in solid state devices, emerged with the discovery of giant magnetoresistance in 1985 and has since enjoyed much commercial and fundamental success. One of the central challenges in the field is transporting electron spin coherently over device-sized distances, and it is here that graphene is expected to be useful. With its low spin-orbit and hyperfine interactions, spin waves suffer little dissipation in graphene, and hence it seems an ideal material for spintronics. However, graphene is non-magnetic, and hence any magnetic interactions must be created by adding impurities or exploiting defects. Furthermore, since it has only been discovered very recently, the fundamental properties of graphene are still under investigation.
Keywords: Physics, Ph.D.; PhD Trinity College Dublin, 2016